2008
DOI: 10.7155/jgaa.00165
|View full text |Cite
|
Sign up to set email alerts
|

C-Planarity of C-Connected Clustered Graphs

Abstract: We present the first characterization of c-planarity for c-connected clustered graphs. The characterization is based on the interplay between the hierarchy of the clusters and the hierarchies of the triconnected and biconnected components of the underlying graph. Based on such a characterization, we provide a linear-time c-planarity testing and embedding algorithm for c-connected clustered graphs. The algorithm is reasonably easy to implement, since it exploits as building blocks simple algorithmic tools like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…1: if G has no internal vertex then 2: 5: Γ (C) ← the drawing obtained by applying Algorithm 2 on C and Γ (C o ); 6: else 7: apply Algorithm 5 on C, obtaining either three paths P u , P v , and P z , or two paths P u and P v ; 8: for 2 ≤ i ≤ U − 1 do 9: σ (u i ) ← the unique child of σ (u i ); 10: end for 11: for 2 ≤ i ≤ V − 1 do 12: σ (v i ) ← the unique child of σ (v i ); 13: end for 14: if Algorithm 5 on C returns three paths P u = (u 1 , . .…”
Section: Input: C(g T ) and γ (C O )mentioning
confidence: 99%
“…1: if G has no internal vertex then 2: 5: Γ (C) ← the drawing obtained by applying Algorithm 2 on C and Γ (C o ); 6: else 7: apply Algorithm 5 on C, obtaining either three paths P u , P v , and P z , or two paths P u and P v ; 8: for 2 ≤ i ≤ U − 1 do 9: σ (u i ) ← the unique child of σ (u i ); 10: end for 11: for 2 ≤ i ≤ V − 1 do 12: σ (v i ) ← the unique child of σ (v i ); 13: end for 14: if Algorithm 5 on C returns three paths P u = (u 1 , . .…”
Section: Input: C(g T ) and γ (C O )mentioning
confidence: 99%
“…The problem can be seen as a hierarchical variant of planarity testing; a problem for which a linear time algorithm has been known for a long time [30]. In the extensive literature devoted to c-planarity and its variants, the complexity status of only restricted special cases has been established, most notably in [2,5,17,27], see also the somewhat outdated survey [16]. The c-planarity problem is formally stated as follows.…”
Section: Introductionmentioning
confidence: 99%
“…An overview on the classical c-planarity problem can be found in [11,19,5]. Dahlhaus [12] and later Cortese et al [11] showed, that c-planarity of hierarchically clustered graphs can be solved in linear time if each cluster induces a connected subgraph. Their approaches make use of the decomposition of the graph into 3-connected components as represented by BC-and SPQR-trees.…”
Section: Introductionmentioning
confidence: 99%